The truth of ecology : nature, culture, and literature in America - Phillips, Dana, 1958- (Oxford University Press, 2003)
A wide-ranging appraisal of environmental thought. It explores such topics as the history of ecology, radical science studies and ecology, the need for greater theoretical sophistication in ecocriticism, the dubious legacy of Thoreau, and the contradictions of contemporary nature writing.